Spatiotemporal Drought Monitoring Using Remote Sensing Technique in Babel-Iraq - Atiyah, Hiba Akram; Khazael, Sajaa M.; Makhool, Assel Qaddoori (Iraqi Journal of Science, 2023)
Drought is one of the most natural hazards that may harm human life and property under different weather and environmental conditions. This study used remote sensing data to monitor agricultural and meteorological drought in Babel Governorate. Drought maps were drawn using Landsat 8 images based on Normalized Difference Vegetation Index (NDVI) for 2015, 2018, and 2021. The meteorological drought was assessed using a standardized precipitation index (SPI 12) for the same years. The results showed that the SPI-12 indicated near-normal drought types in 2015 and 2018, whereas SPI values showed a lower value in 2021. Two drought categories were identified which were moderate drought and severe drought. The NDVI results showed that the vegetation area decreased in 2021 by 9 % in comparison to 2015. This result could help the government planners to develop and manage the drought impacts.